Facet-dependent generation of superoxide radical anions by ZnO nanomaterials under simulated solar light. Issue 12 (13th November 2018) - Wang, Qianwu; Zhou, Huaxi; Liu, Xinlei; Li, Tong; Jiang, Chuanjia; Song, Weihua; Chen, Wei
Abstract : The capability of ZnO nanomaterials to generate reactive oxygen species under solar light, which is critical for their photocatalytic applications and may affect their environmental implications, can be substantially influenced by exposed facets. Abstract : The capability of semiconductor nanomaterials to generate reactive oxygen species (ROS) under solar irradiation, which is critical for their photocatalytic applications and may affect their environmental implications, can be substantially influenced by intrinsic nanomaterial properties, particularly exposed facets. However, the specific mechanisms controlling the facet-dependent ROS generation of widely used semiconductor nanomaterials, e.g. zinc oxide (ZnO), are not well understood. Here, we report that under identical irradiation conditions a ZnO nanoplate material with predominantly exposed 0001 facets generates nearly four times as much superoxide radical anions (O2 ˙ − ) as a porous ZnO nanosheet material with predominantly exposed 101̄0 facets, even though the former possesses much smaller specific surface area. The enhanced O2 ˙ − generation of ZnO nanoplates with exposed 0001 facets can be ascribed to the following two aspects: (1) the 0001 facets, which contain more abundant coordinatively unsaturated zinc atoms, can adsorb a greater amount of molecular oxygen (O2 ), and (2) the more negative conduction band potential of the 0001 facets can provide stronger thermodynamic driving force for the reduction of surface O2 to O2 ˙ − . The enhanced O2 ˙ − generation resulted in faster photocatalytic degradation of organic contaminants (using tetracycline as a model antibiotic contaminant) and greater bacterial inactivation (using Escherichia coli as a model microorganism). This study further identifies exposed facets as a critical nanomaterial property in dictating the photocatalytic activity and environmental implications of nanomaterials.